2021
DOI: 10.3389/fpsyg.2021.798115
|View full text |Cite|
|
Sign up to set email alerts
|

Financial Performance Under the Influence of the Coronavirus Disease 2019: Effects of Strategic Flexibility and Environmental Dynamics in Big Data Capability

Abstract: This study draws on the dynamic capabilities view and the firm’s big data capability (BDC) in the new economic environment. It constructs an adjusted intermediary model to study the mechanism of BDC, strategic flexibility, and environmental dynamic affecting financial performance. We find that strategic flexibility plays an intermediary role in the “Converse-U” relationship between BDC and financial performance. Environmental dynamics adjust the relationship between BDC and financial performance positively and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 49 publications
0
6
0
Order By: Relevance
“…Economically developed regions also lead the country in terms of system construction and platform construction in terms of results transformation system and supporting settings. For example, Limei Chen et al (2020) [ 24 ] and Weihong Li et al (2022) [ 25 ] found from the perspective of patent operation that Jiangsu Province has greatly promoted the transformation effect of scientific and technological achievements by formulating policy measures with a high degree of fit. Agasisti T et al (2022) [ 26 ] examined how the efficiency of universities is influenced by the characteristics of the regions in which they are located and found that the management efficiency of universities is closely related to the environment in which they are located; specifically, universities in socioeconomically developed regions tend to be more efficient.…”
Section: Analysis Of the Coupling Mechanism Between The Transformatio...mentioning
confidence: 99%
“…Economically developed regions also lead the country in terms of system construction and platform construction in terms of results transformation system and supporting settings. For example, Limei Chen et al (2020) [ 24 ] and Weihong Li et al (2022) [ 25 ] found from the perspective of patent operation that Jiangsu Province has greatly promoted the transformation effect of scientific and technological achievements by formulating policy measures with a high degree of fit. Agasisti T et al (2022) [ 26 ] examined how the efficiency of universities is influenced by the characteristics of the regions in which they are located and found that the management efficiency of universities is closely related to the environment in which they are located; specifically, universities in socioeconomically developed regions tend to be more efficient.…”
Section: Analysis Of the Coupling Mechanism Between The Transformatio...mentioning
confidence: 99%
“…Financial performance refers to the profitability of a firm [27]. In the past, the measurement of financial performance mostly used financial statement indicators, such as Tobin's Q, return on equity, or return on assets [28,29].…”
Section: Financial Performancementioning
confidence: 99%
“…Financial performance is the extent to which a firm's return on investment, customer retention, sales growth rate, and profitability [27]. Most theoretical and empirical studies report that environmental policies are crucial for business performance [41][42][43].…”
Section: The Environmentally Proactive Strategy Adoption and Financia...mentioning
confidence: 99%
“…Brozovic [24] proposed that strategic flexibility refers to the ability of an organization to identify major changes in the external environment, quickly allocate resources to new courses of action in response to these changes, and immediately recognize and take action when it is time to stop or reverse existing resource commitments. Existing empirical studies on strategic flexibility mainly focus on the relationship between strategic flexibility and financial performance [25], enterprise innovation [26], and organizational performance [27], and few studies on the relationship between strategic flexibility and enterprise behavior.…”
Section: Strategic Flexibilitymentioning
confidence: 99%